Burst fractures of the fifth lumbar vertebra: Case series and systematic review. (September 2022) - Cavagnaro, María José; Tavolaro, Celeste; Orenday-Barraza, José Manuel; Farhardi, Dara; Baaj, Ali A.; Bransford, Richard
Highlights: L5 fractures are very rare and deserve to be distinguished from the rest of the spine. Neurological injuries are not correlated with the degree of canal stenosis at L5. After L5 fracture, neurological injuries have a promising prognosis after surgery. The restoration of sagittal imbalance after L5 fracture can be achieved with AC. Nonoperative treatment can be considered in intact patients with good alignment. Abstract: Background: Burst fractures of the fifth lumbar vertebra (L5) are rare injuries and typically occur because of high-energy axial compressive load. Their unique anatomy and biomechanical characteristics distinguish them from other lumbar spine injuries. To the best of our knowledge, the treatment strategies for L5 burst fractures have not been thoroughly described. The aims of this case series and systematic review were to highlight the treatment strategies and outcomes of the L5 burst fractures. Methods: We performed a retrospective case series of 8 patients treated for burst L5 fractures in our institution between 2005 and 2020. Additionally, a systematic review via PubMed and Cochrane Library databases according to PRISMA guidelines was performed to review L5 burst fractures treatment strategies. Only Articles in English with full text available were included. The references of the selected studies were checked to find all possible related articles. Treatment strategies were conservative, posterior segmental instrumentation and fixation (PSIF), PSIF with anterior corpectomy (AC), and PSIF with posterior corpectomy (PC). Outcomes measures included neurological status, radiological regional alignment, and complications. Results: A total of 1449 publications were found, and 29 articles were finally selected for analysis. Of those, 15 were retrospective case reports, and 14 were retrospective case series. One hundred and sixty-nine patients were found in the review. The author's eight cases were added to the found in the literature for a methodological quality assessment. There were 52 (29%) patients managed non-operative, and 125 (71%) underwent surgery. One-hundred-two patients were neurologically intact, of whom 46 were managed non-operative. Canal compromise in intact patients ranged between 20 and 90%. Posterior segmental fixation and instrumentation with decompression was the preferred surgical strategy in patients with neurological deficits. Patients with combined anterior column restoration and anterior approach showed vertebral height and lordosis restoration. A 79% of the operative treated group reported neurological improvement. Patients with pre-operative neurological deficit managed non-operative reported the highest rate of complications (33.3%). Conclusion: In the setting of L5 burst fractures, neurological injuries have a promising prognosis after surgery and are not correlated with the degree of canal stenosis. The compromise of the L5 vertebra affects the sagittal balance and its restoration can be achieved with an anterior corpectomy. Nonoperative management can be considered in cases of reasonable alignment, and no neurologic deficit.